Understanding the control strategies effective against the esca leaf stripe symptom: the edge hypothesis - DEL FRARI, Giovanni; CALZARANO, Francesco; BOAVIDA FERREIRA, Ricardo (Phytopathologia Mediterranea, 2022)
A peculiar symptom that may develop in grapevines affected by wood pathogens involved in the esca complex of diseases is the leaf stripe symptom, which also gives the name to the Grapevine Leaf Stripe Disease. Multiple studies have revealed strong links between fungal presence, wood symptomatology and expression of the leaf stripe symptom. However, numerous other factors have been shown to play roles in symptom onset, incidence, severity and yearly fluctuation of this disease. While the factors triggering the leaf stripe symptom are still under investigation, three control strategies have been proven effective for substantially reducing its expression, namely trunk surgery, and applications of sodium arsenite or a fertilizer mixture. These control strategies are examined here, including their (putative or confirmed) modes of action, and how they may influence the leaf stripe symptom development. In this article, we also propose the ‘edge’ hypothesis to tentatively explain symptoms onset, keeping in consideration past knowledge and recent advances in the understanding of the esca leaf stripe symptom. Ultimately, it is our intention to offer food-for-thought and stimulate debate within the phytopathological community.